2016
DOI: 10.1039/c6ra07095g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled peptide microspheres for sustainable release of sulfamethoxazole

Abstract: Porous peptide microspheres have been used for the loading and sustained release of the bacteriostatic antibiotic sulfamethoxazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…26 The results from the molecular dynamics study of a series of Ac-(Aib) n -NHMe (where Ac, acetyl; n ¼ 5-7, 10; NHMe ¼ methylamino) were recently published as well. 27 A range of publications reported the synthesis of Aib-containing peptides via solution 22,[31][32][33] or solid-phase techniques. 21,[34][35][36][37] Recently, Tsuchiya and Numata described also the enzymatic synthesis of hydrophobic polypeptides based on Ala and Aib.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 The results from the molecular dynamics study of a series of Ac-(Aib) n -NHMe (where Ac, acetyl; n ¼ 5-7, 10; NHMe ¼ methylamino) were recently published as well. 27 A range of publications reported the synthesis of Aib-containing peptides via solution 22,[31][32][33] or solid-phase techniques. 21,[34][35][36][37] Recently, Tsuchiya and Numata described also the enzymatic synthesis of hydrophobic polypeptides based on Ala and Aib.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembling properties of Aib-containing peptides were the subject of many investigations. [28][29][30][31][32][39][40][41] In particular, Kimura and co-workers synthesized peptide nanotubes of different size . 40 More recently, Haldar and coworkers demonstrated that Boc-Phe-Aib-Gabu-OMe and Boc-Tyr-Aib-Gabu-OMe (Gabu, g-aminobutyric acid) are able to form polydisperse microspheres with a diameter of ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations